(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
Serratia marcescens is a significant opportunistic pathogen that affects a variety of hosts, including invertebrates, plants, and mammals. It is linked to a wide range of clinical illnesses, including pneumonia, keratitis, meningitis, urinary tract infections, and wound infections. The present research aimed to estimate the immune response of rabbits immunized with whole cell sonicated antigen of Serratia marcescens, killed whole cell antigen of S. marcescens and lipopolysaccharide extracted from Citrobacter freundii against Serratia marcescens infection; a challenge dose was 8x106 CFU/ml. Thirty five (35) white male rabbits aged between 6-8 weeks, were divided randomly into five groups (7 rabbits each) and ELISA test was performed. The first group received a subcutaneous (S/C) immunization with WCSAg-S and LPS-C (1000 g/mL) vaccine. The second group received KWCA-S (9 x 108 CFU/mL) and LPS-C (1000 g/mL) vaccinations. The sole vaccine given to the third group was WCSAg-S (1000 g/mL). LPS-C (1000 g/ml) was used to immunize the fourth group. 1 mL of PBS was given subcutaneously into the fifth group (the negative control) (pH 7.2). The rabbits received booster doses of the same antigens after 14 days. Following 21, 35, 49, and 53 days of vaccination, the inoculated animals demonstrated significant changes (P <0.05) in IL-2 and IL-10 compared to the negative control group. In conclusion, the 3 rd group immunized with WCSA-S only was able to promote stronger humoral and cellular immune responses against Serratia marcescens infection in comparison with the other groups>